Microrobots in Brewery: Dual Magnetic/Light-Powered Hybrid Microrobots for Preventing Microbial Contamination in Beer - Villa, Katherine; Vyskočil, Jan; Ying, Yulong; Zelenka, Jaroslav; Pumera, Martin (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
Yeasts play a key role in the production of alcoholic beverages by fermentation processes. However, because of their continuous growth, they commonly cause spoilage of the final product. Herein, we introduce dual magnetic/light-responsive self-propelled microrobots that can actively move in a beer sample and capture yeast cells. The presence of magnetic nanoparticles on the surface of the microrobots enables their magnetic actuation under fuel-free conditions. In addition, their photoactivity under visible-light irradiation leads to an overall enhancement of their swimming and yeast removal capabilities. It was found that after the application of the microrobots into a real unfiltered beer sample, these micromachines were able to remove almost 100 % of residual yeasts. In addition, these microrobots could also be added at the initial step of the fermentation process without altering the final beer properties, such as alcohol level, color, and pH. This work demonstrates the potential of using externally actuated microrobots as an innovative and low-cost solution for avoiding yeast spoilage in complex liquid environments, such as alcoholic beverages. Therefore, these autonomous self-propelled microrobots open new avenues for future applications in the food industry.
Keywords: micromotors; vanadáty; yeast removal; fermentace; světlo; Beer; pivo; Bismuth; magnetické pole; bismut; antibakteriální látky; photocatalysis; Light; Fermentation; fermentation; Anti-Bacterial Agents; peroxid vodíku; kontaminace potravin; Food Contamination; Vanadates; mikrosféry; Saccharomyces cerevisiae; Photochemical Processes; beer spoilage; magnetické nanočástice; Magnetic Fields; Hydrogen Peroxide; Magnetite Nanoparticles; Microspheres; fotochemické procesy